2020
DOI: 10.3389/fnmol.2020.534238
|View full text |Cite
|
Sign up to set email alerts
|

Food Anticipatory Activity on Circadian Time Scales Is Not Dependent on Central Serotonin: Evidence From Tryptophan Hydroxylase-2 and Serotonin Transporter Knockout Mice

Abstract: A number of studies implicate biogenic amines in regulating circadian rhythms. In particular, dopamine and serotonin influence the entrainment of circadian rhythms to daily food availability. To study circadian entrainment to feeding, food availability is typically restricted to a short period within the light cycle daily. This results in a notable increase in pre-meal activity, termed "food anticipatory activity" (FAA), which typically develops within about 1 week of scheduled feeding. Several studies have im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…When the availability of food is time restricted, the dorsal striatum is proposed to function as a food‐entrained oscillator, resulting in food anticipatory activity with a circadian rhythm that is synced to the food availability time schedule 134 . The role of serotonin signaling in food anticipatory activity is debated: where previous studies have suggested that whole‐brain serotonin signaling suppresses the development of food anticipatory activity, 135,136 a more recent study reported food anticipatory activity to be independent of serotonin signaling 137 . Serotonergic signaling in the dorsal striatum is more strongly related to the regulation of motor behavior, and perturbed serotonergic signaling within this region is associated with several pathological motor conditions 138,139 …”
Section: Functional Organization Of Serotonergic Signaling In Eating Behaviormentioning
confidence: 99%
“…When the availability of food is time restricted, the dorsal striatum is proposed to function as a food‐entrained oscillator, resulting in food anticipatory activity with a circadian rhythm that is synced to the food availability time schedule 134 . The role of serotonin signaling in food anticipatory activity is debated: where previous studies have suggested that whole‐brain serotonin signaling suppresses the development of food anticipatory activity, 135,136 a more recent study reported food anticipatory activity to be independent of serotonin signaling 137 . Serotonergic signaling in the dorsal striatum is more strongly related to the regulation of motor behavior, and perturbed serotonergic signaling within this region is associated with several pathological motor conditions 138,139 …”
Section: Functional Organization Of Serotonergic Signaling In Eating Behaviormentioning
confidence: 99%
“…Serotonin ablation did not impact the typical day/night fluctuations in mouse activity observed as a response to changes in environmental light. Despite known interactions between serotonin and circadian control systems (regulation of the sleep-wake cycle) and their respective roles in the expression of seasonal mood disorders for instance (Gallardo et al, 2020), this result confirms the role of a larger neurobiological network for the regulation of these homeostatic processes. Moreover, the lack of congenital serotonin did not abolish the expression of any specific behaviour in mice, however it drastically affected their relative frequencies.…”
Section: Discussionmentioning
confidence: 55%
“…Pharmacologically increasing serotonin levels by a selective serotonin reuptake inhibitor, fluvoxamine, suppressed FAA, whereas decreasing serotonin levels by a tryptophan hydroxylase inhibitor enhanced FAA in mice ( Rozenblit-Susan et al, 2016 ). However, FAA was unaffected by time RF in both serotonin transporter and tryptophan hydroxylase-2 KO mice, which indicated that serotonin is not necessary for regulating FAA ( Gallardo et al, 2020 ). Some studies suggested that a neuropeptide knows as orexin or hypocretin may be involved in the regulation of food anticipation behavior.…”
Section: Discussionmentioning
confidence: 99%